2005
DOI: 10.1246/cl.2005.676
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Photochromic Durability at the Single-molecule Level

Abstract: A fluorescent photochromic diarylethene, which has excellent photostability and efficient fluorescence switching character even at the single-molecule level, was synthesized and the fatigue resistant property was quantitatively evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Therefore, compounds 4 - Et and 11 were not expected to be more photostable than compound 1b . A rough estimation of the average number of switching cycles may be based on the observation that SMs of fluorescent dyes (including photochromic fluorescent DAEs) generally decompose after 10 6 –10 7 excitation cycles. If we consider the values of the isomerization quantum yields for one complete cycle (OF–CF–OF) of compounds 4-Et and 11 (Table ), we may estimate that the average number of switching cycles is expected to be on the order of ∼10. Evaluation of the fatigue resistance of compounds 4-Et and 11 in diluted methanolic and aqueous solutions showed that they can endure several tens of cycles (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, compounds 4 - Et and 11 were not expected to be more photostable than compound 1b . A rough estimation of the average number of switching cycles may be based on the observation that SMs of fluorescent dyes (including photochromic fluorescent DAEs) generally decompose after 10 6 –10 7 excitation cycles. If we consider the values of the isomerization quantum yields for one complete cycle (OF–CF–OF) of compounds 4-Et and 11 (Table ), we may estimate that the average number of switching cycles is expected to be on the order of ∼10. Evaluation of the fatigue resistance of compounds 4-Et and 11 in diluted methanolic and aqueous solutions showed that they can endure several tens of cycles (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that some carbocyanine dyes also act as efficient reversible photoswitches at the singlemolecule level upon irradiation with red and green light. 11, 12 Although the efficiency of photoswitching at the single-molecule level has been improved greatly in the past few years for the diarylethene derivatives, 13 it is still below the excellent values reported for the ensemble photochromic reaction. 14 Moreover, in the case of cabocyanine dyes, the mechanism of the photoswitching observed at the single-molecule level is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ratio (contrast) between the emission intensity measured after the photochromic transformation and that measured before is related to the composition of the photostationary state. In most instances, both interconvertible forms are present at the photostationary state and, hence, these photoswitchable systems generally have modest contrast ratios with few notable exceptions. In addition, their excitation dynamics can encourage competitive deactivation pathways and the gradual degradation of the fluorescent and/or photochromic components with the number of switching cycles. Thus, the evolution of these molecular and supramolecular switches into functional materials for practical applications requires the identification of innovative operating principles that would ensure fluorescence photoswitching with improved contrast ratios and fatigue resistances.…”
mentioning
confidence: 99%